Room service - Alers, Rochelle (Alers, Rochelle. Innkeepers., 2018)
New Yorker Jasmine Washington had a successful interior design business, a high-powered marriage, and a chance at motherhood<U+2014>until her perfect husband betrayed her big-time. Now starting from scratch, the Asian and African-American stunner is tackling a lifetime opportunity: co-managing her friend<U+2019>s new luxury inn about to open in the Garden District. The last thing Jasmine needs is romance. New Orleans' most eligible bachelor, investment banker Cameron Singleton, begs to differ. Cameron challenges Jasmine<U+2019>s cautious ways, teases her back into having real fun<U+2014>and makes one sexy, utterly irresistible Mr. Right Now. But their passionate nights soon result in a surprise bonus. . . . Even though Cameron insists on being there for Jasmine, can she really believe his love is the real thing? Can she shake the past and design a completely new life? And is there really only one way to find out?